Caracterização morfológica de espécies de Hemerobius Linnaeus, 1758 (Neuroptera, Hemerobiidae) associadas a cultivos de café (Coffea arabica L.), milho (Zea mays L.) e erva-mate (Ilex paraguariensis St. Hill.) - Lara, Rogéria Inês Rosa; Freitas, Sérgio de [UNESP] (Sociedade Brasileira de Entomologia, 2003)
The predators were collected in mate crop in Cascavel and São Mateus do Sul, Paraná, Brazil and some other additional specimens in coffee and maize crops in Ribeirão Preto, São Paulo, Brazil. Illustrations obtained by SEM are given by the first time to the principal structures. Three species of Hemerobius were identified: H. bolivari Banks, 1910; H. domingensis Banks, 1941 and H. gaitoi Monserrat, 1996. H. domingensis is recorded for the first time to Brazil.
Morphologic characterization of the Hemerobius Linnaeus, 1758 species (Neuroptera, Hemerobiidae) associated to the cultivations of coffee (Coffea arabica L.), maize (Zea mays L.) and mate (Ilex paraguariensis St. Hill.)
Keywords: Brazil; Hemerobiidae; Hemerobiinae; Morphology